2017
DOI: 10.1007/s00330-017-4732-0
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer imaging to discriminate between low- and high-grade gliomas: added value to apparent diffusion coefficient and relative cerebral blood volume

Abstract: Objectives To evaluate the added value of amide proton transfer (APT) imaging to the apparent diffusion coefficient (ADC) from diffusion tensor imaging (DTI) and the relative cerebral blood volume (rCBV) from perfusion magnetic resonance imaging (MRI) for discriminating between high- and low-grade gliomas. Methods Forty-six consecutive adult patients with diffuse gliomas who underwent preoperative APT imaging, DTI and perfusion MRI were enrolled. APT signals were compared according to the World Health Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 33 publications
8
93
0
Order By: Relevance
“…However, few studies have examined glioma grading with multiparametric imaging that included APT imaging and PWI or DWI. 10,16 To the best of our knowledge, our investigation represents the first study to show the utility of multiparametric analysis, including APT and PET, in the preoperative grading of gliomas.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 90%
See 4 more Smart Citations
“…However, few studies have examined glioma grading with multiparametric imaging that included APT imaging and PWI or DWI. 10,16 To the best of our knowledge, our investigation represents the first study to show the utility of multiparametric analysis, including APT and PET, in the preoperative grading of gliomas.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 90%
“…This study confirmed that APT imaging can be used for grading glial tumors, with a diagnostic accuracy comparable with that of other imaging biomarkers derived from DWI and FDG-PET. Previous studies have shown the diagnostic accuracy of APT imaging to be comparable with DSC-PWI, 13,16 and better than contrastenhanced T1-weighted imaging. 22 As in previous studies, our results also demonstrated excellent interrater reproducibility in the measurement of APT.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 96%
See 3 more Smart Citations